Conqueror : a novel of Kublai Khan - Iggulden, Conn (Delacorte Press, 2012)
Tells the story of the rise of Kublai Khan to take over his grandfather Genghis Khan's empire, as well as China, in a novel that focuses on the brutal competition between Kublai and his three brothers.